Effect of different levels of pollen shedders on productivity of pearl millet (Pennisetum glaucum) hybrids - KAPOOR, R L; SAGAR, PRAM; NIJHAWAN, D C; YADAV, YASHPAL (The Indian Journal of Agricultural Sciences, 2013)
Six combinations of pollen shedden, created artificially by blending the seed of pearl millet (Pennisetum glaucum (L.) R. Br, emend. Stuntz] hybrid ’IIHB 50’ (’MS 81A’ X ’H 90/4-5’) with its seed parent ’MS 81A’, viz99% H + 1% F(H.hybrid;F,female), 98% H+2% F,97% H+3% F,95% H+5% F,93% H + 7% F, 90% H + 10% F, and 2 controls (100 % H, 100 % F) simulating the conditions naturally occurring in seed-production plots were evaluated at Hisar and Bawal during 1988. The trial with these combinations along with 3 hybrids (’HHB 50’, ’HHB 67’ and ’HHB 68’) based on 3 different male-sterile lines CMS SlA’, ’MS 843A’ and ’MS 842A’) was repeated in 1989. Various pollen-shedder combinations were at par among themselves as well as with the control (100 % H), irrespective of the hybrid,location and year. Substantial reduction in such ancillary characters as plant height (cm), ear length (cm), effective tillers and seed set (%) on female plants was recorded in the female plants in the various pollen-shedder combinations. The vigour of hybrid plants suppressed the weak female (inbred) seedlings. As high as 10% pollen shedders had no effect on the potential productivity of the hybrid seed. It strongly supports the relaxation of seed-certification standards (